2017
DOI: 10.1111/pan.13180
|View full text |Cite
|
Sign up to set email alerts
|

Childhood preoperative anxiolysis: Is sedation and distraction better than either alone? A prospective randomized study

Abstract: Both pharmacological premedication and video distraction are effective strategies for controlling preoperative childhood anxiety. The combination of midazolam and Digital Video-Disk player was not better than either alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 31 publications
1
40
0
3
Order By: Relevance
“…2,4,44 However, another study revealed that both pharmacological and nonpharmacological preparation can reduce preoperative anxiety but that nonpharmacological intervention did not reduce or affect the dosage of sedative drugs when used as a combination. 50 Our study had some limitations. First, we did not record baseline variables, such as the number of previous bone marrow aspiration procedures, which might influence patients' levels of anxiety.…”
Section: Discussionmentioning
confidence: 90%
“…2,4,44 However, another study revealed that both pharmacological and nonpharmacological preparation can reduce preoperative anxiety but that nonpharmacological intervention did not reduce or affect the dosage of sedative drugs when used as a combination. 50 Our study had some limitations. First, we did not record baseline variables, such as the number of previous bone marrow aspiration procedures, which might influence patients' levels of anxiety.…”
Section: Discussionmentioning
confidence: 90%
“…The emergence delirium was measured in two studies [27] [30]. In both studies the authors used PAED to measure children emergence delirium and both studies included a premedication control group.…”
Section: The Effectiveness Of Video Distraction Intervention On Childmentioning
confidence: 99%
“…Não houve diferença entre os grupos, o que mostra que medidas não farmacológicas para diminuição da ansiedade são tão eficazes quanto medidas farmacológicas. Em um estudo similar, Sola et al 73 comparou midazolam, midazolam com vídeo e vídeo isoladamente como medidas de diminuição da ansiedade pré-operatória. Os autores também não observaram diferença na ansiedade pré-operatória medida pela escala mYPAS e por uma escala visual analógica.…”
Section: Questões Práticasunclassified